Effects of gut microbiota manipulation on ex vivo lipolysis in human abdominal subcutaneous adipocytes. (3rd April 2018) - Jocken, Johan W. E.; Reijnders, Dorien; Canfora, Emanuel E.; Boekschoten, Mark V.; Plat, Joghum; Goossens, Gijs H.; Blaak, Ellen E.
ABSTRACT: The intestinal microbiota may contribute to the development of obesity by affecting host lipid metabolism and insulin sensitivity. To investigate the effects of microbiota manipulation on ex vivo basal and β-adrenergically-stimulated lipolysis in human adipocytes, 36 obese men were randomized to amoxicillin (broad-spectrum antibiotic), vancomycin (narrow-spectrum antibiotic) or placebo treatment (7 d, 1500 mg/d). Before and after treatment, ex vivo adipose tissue lipolysis was assessed under basal conditions and during stimulation with the non-selective β-agonist isoprenaline using freshly isolated mature adipocytes. Gene (targeted microarray) and protein expression were analyzed to investigate underlying pathways. Antibiotics treatment did not significantly affect basal and maximal isoprenaline-mediated glycerol release from adipocytes. Adipose tissue β-adrenoceptor expression or post-receptor signalling was also not different between groups. In conclusion, 7 d oral antibiotics treatment has no effect on ex vivo lipolysis in mature adipocytes derived from adipose tissue of obese insulin resistant men.